APPLICATION OF DIGITAL INFINITE IMPULSE RESPONSE FILTER TO REDUCE POWER-LINE INTERFERENCE NOISE ON ECG 12 LEAD (TRANSVERSAL TEACHING) - Denis Kurniar Wicaksono (Jurnal Teknokes, 2023)
The development of cardiac diagnostic tools continues to grow. As we know that heart disease has the highest mortality rate and further action is needed against the disease. The tool commonly used to detect heart disease is the EKG. The use of analog filters is starting to be abandoned because in its use it can only use a limited order and will have an impact on the cost factor and circuit size, the use of analog filters has been replaced by digital filters. Digital filter technique is the most suitable technique to help improve the quality of the ECG signal. The purpose of this study is to reduce measurement errors in reading the ECG measurement results by reducing noise in the ECG signal. The contribution of this research is to know the configuration of the butterworth digital filter which is effective for reducing noise in the use of 12 Lead ECG equipment. This was achieved by making a 12 Lead ECG device using the AD8232 sensor. In this study, the output of AD8232 will be processed with a digital Butterworth filter on the microcontroller and Delphi which will then be displayed on the Delphi application using a Personal Computer and a comparative analysis of the results will be carried out using the Matlab application. With this research, it is hoped that the filter arrangement with the appropriate order for the electrocardiogram device will be obtained. From this study, it can be concluded that the 12-lead electrocardiogram in this study was designed using the AD8232 module and a Butterworth digital filter displayed on a PC using the Delphi7 application to facilitate the filter analysis process used. The results of this study are expected to reduce diagnostic errors in reading the results of ECG measurements and can also be used as a reference for further research to be better.